-5x-3=-2x+8

Simple and best practice solution for -5x-3=-2x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-3=-2x+8 equation:


Simplifying
-5x + -3 = -2x + 8

Reorder the terms:
-3 + -5x = -2x + 8

Reorder the terms:
-3 + -5x = 8 + -2x

Solving
-3 + -5x = 8 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-3 + -5x + 2x = 8 + -2x + 2x

Combine like terms: -5x + 2x = -3x
-3 + -3x = 8 + -2x + 2x

Combine like terms: -2x + 2x = 0
-3 + -3x = 8 + 0
-3 + -3x = 8

Add '3' to each side of the equation.
-3 + 3 + -3x = 8 + 3

Combine like terms: -3 + 3 = 0
0 + -3x = 8 + 3
-3x = 8 + 3

Combine like terms: 8 + 3 = 11
-3x = 11

Divide each side by '-3'.
x = -3.666666667

Simplifying
x = -3.666666667

See similar equations:

| 10=14+4x | | x+4=3x-2-6 | | 10+3(x-2)=31 | | 17.9-3h+9+4h=12.3 | | -3x+2x-6x=49 | | 12x^2+47x-42=0 | | 15x-3x=72 | | 12x+13x=50 | | -x+2x=8 | | 3(3m-2)=5(4-m) | | 3x+4x=84 | | 5x=4x | | 2s+11=5s+2 | | -(2a-10)=-6 | | 9m-6=20-5m | | 1-v+4=10 | | (x+4)=(x-7) | | z^2-11z=42 | | x^2+4x+4=16 | | 4(2p+7)=3(p-1) | | 1+4p-3p=6 | | -x^2+5x-2=0 | | 8p+28=3p-3 | | X+3+x+8=22 | | 2=-6x+4 | | X^2-12x-18=0 | | 3(5k+1)=6(3k-2) | | 3(5r+1)=6(3k-2) | | -3x+7=3x-17 | | 80v=40 | | 2b+16=4b-8 | | 15k+3=18k-12 |

Equations solver categories